Experimental Investigation and Modelling of Moisture Absorption Effect on Palmyra Fibre - Kaur, Harpreet (My University, 2018)
Studies on the use of natural fibres as replacement to man-made fibre in fibre-reinforced composites have increased and opened up further industrial possibilities. Palmyra fibre is used as a fibre reinforcement material. Natural fibres have the advantages of low density, low cost, and biodegradability. However, the main disadvantages of natural fibres in composites are the poor compatibility between fibre and matrix and the relative high moisture sorption. Therefore, chemical treatments are considered in modifying the fibre surface properties. In this research, the different chemical modifications on Palmyra fibres for use in natural fibre-reinforced composites are considered. Chemical treatments including 5%alkali, 1% stearic acid and 4% stearic acid are performed. The chemical treatment of fibre aimed at improving the adhesion between the fibre surface and the polymer matrix may not only modify the fibre surface but also improves the hydrophobic properties. Water absorption of composites is reduced and modelling analysis has been done using Abaqus.
Keywords: Natural Fibre; Palmyra Fibre; Moisture Absorption; Chemical modifications; Mass Gain Analysis